Perceptions of Transformational Teacher towards Increasing Teacher Pedagogical Competency in Rokan Hulu Regency - Sheldiha, Duwanita; Darmansyah, Darmansyah; J, Fetri Yeni; Pratiwi, Rahmi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Pedagogical competence is one type of competence that teachers absolutely need to master. Pedagogical competence is basically the teacher's ability to manage student learning. Pedagogical competency is a distinctive competency, which will differentiate teachers from other professions and will determine the level of success of the learning process and outcomes of their students. Based on the results of an interview with one of the practicing teachers, it is clear that teachers still lack understanding of this pedagogical competency. Therefore, this research aims to describe improving the pedagogical competence of driving teachers who have taken part in the Driving Teacher Education Program (PPGP) training in Rokan Hulu Regency. This research uses descriptive quantitative research which aims to describe the actual situation of the research population based on samples taken from data obtained in the form of numbers. The sample for this research was 45 teachers from class 10 of Rokan Hulu district. Data collection was carried out using a questionnaire consisting of 30 statement items which had previously been validated.The results of this research show that the perception of driving teachers towards increasing the pedagogical competence of teachers in Rokan Hulu Regency is understanding the character of students with a percentage of 81.76% is in the very good category, mastery of learning theory with a percentage of 70.09% is in the good category, reflection on learning with a percentage of 83.98% is in the very good category, the use of technology in learning with a percentage of 80.28% is in the good category and evaluation of learning outcomes with a percentage of 72.96% is in the good category. Based on the findings above, it can be concluded that the driving teacher education program can improve teachers' pedagogical competence, to create more effective learning in schools.